Design of Potent Mannose 6‐Phosphate Analogues for the Functionalization of Lysosomal Enzymes To Improve the Treatment of Pompe Disease. Issue 47 (24th October 2016) - El Cheikh, Khaled; Basile, Ilaria; Da Silva, Afitz; Bernon, Coralie; Cérutti, Pierre; Salgues, Frédéric; Perez, Marc; Maynadier, Marie; Gary‐Bobo, Magali; Caillaud, Catherine; Cérutti, Martine; Garcia, Marcel; et al.
Abstract: Improving therapeutics delivery in enzyme replacement therapy (ERT) for lysosomal storage disorders is a challenge. Herein, we present the synthesis of novel analogues of mannose 6‐phosphate (M6P), known as AMFAs and functionalized at the anomeric position for enzyme grafting. AMFAs are non‐phosphate serum‐resistant derivatives that efficiently bind the cation‐independent mannose 6‐phosphate receptor (CI‐M6PR), which is the main pathway to address enzymes to lysosomes. One of the AMFAs was used to improve the treatment of the lysosomal myopathy Pompe disease, in which acid α‐glucosidase (GAA) is defective. AMFA grafting on a M6P‐free recombinant GAA led to a higher uptake of the GAA in adult Pompe fibroblasts in culture as compared to Myozyme, the M6P recombinant GAA. Moreover, the treatment of Pompe adult mice with the AMFA‐grafted recombinant enzyme led to a remarkable improvement, even at low doses, in muscle functionality and regeneration, whereas Myozyme had limited efficacy. Abstract : Crafty grafting : Mannose 6‐phosphate (M6P) derivatives functionalized at the anomeric position (AMFAs) were designed to target recombinant enzymes to lysosomes. When one such AMFA was grafted on human acid α‐glucosidase, the therapeutic activity of the modified enzyme against Pompe disease was remarkably improved in adult mice as compared to that of the enzyme (containing natural M6P) authorized for the treatment of Pompe disease.